SYSTEMATIC LITERATURE REVIEW: MODEL PEMBELAJARAN MATEMATIKA PADA KEMAMPUAN LITERASI MATEMATIKA SISWA SEKOLAH MENENGAH - Muslim, Audra Pramitha; Darhim, Darhim (Universitas PGRI Sumatera Barat, 2023)
This study aims to analyze the mathematics learning model that is widely used by researchers to improve high school students' mathematical literacy. The research method used in this article is System Literature Review (SLR). The sample consists of 24 research results on the application of mathematics learning models that can improve high school students' mathematical literacy skills. This sample was obtained from indexed journals published in the 2018-2022 period. This research was conducted in accordance with related inclusion criteria, with the research question being what learning model is the most popular used to improve high school student's mathematical literacy? And what level of education do most mathematical literacy tests do? Through the SLR method it was found that the learning model that is widely used to improve mathematical literacy skills is the Problem Based Learning (PBL) learning model. With the main characteristics of this model, namely: a learning model that sharpens many student skills and can also be implemented in everyday life and starts learning with a main question by planning a project to solve these problems in finding the concept of the subject matter being . The level of education that uses the most mathematical literacy is junior high school (SMP) students. With the main characteristics of this model, namely: a learning model that sharpens many student skills and can also be implemented in everyday life and starts learning with a main question by planning a project to solve these problems in finding the concept of the subject matter being . The level of education that uses the most mathematical literacy is junior high school (SMP) students. With the main characteristics of this model, namely: a learning model that sharpens many student skills and can also be implemented in everyday life and starts learning with a main question by planning a project to solve these problems in finding the concept of the subject matter being . The level of education that uses the most mathematical literacy is junior high school (SMP) students.